(untitled) (Intent Research Scientific Journal, 2023)
This article analyzes the characterization of quality as a leading factor in the development of Higher Education. Also, the current socio-economic processes are presented to higher education and each educational organization with innovative tasks of social significance aimed not only at education, upbringing, development of the educational person, but also at socialization of the population, preservation of cultural values, satisfaction of the needs of the employment, labor market.